(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides a comprehensive analysis of the metafiction (or meta-narrative) genre, using Haruki Murakami’s novel "1Q84" as a primary example. It highlights how metafiction diverges from conventional storytelling by intentionally drawing attention to its own constructed nature and fictionality. The study meticulously examines core metafictional components within "1Q84," supported by academic illustrations. These elements include the presence of text embedded within the narrative (exemplified by the "Air Chrysalis" book), the inherent subjectivity and ambiguous portrayal of reality (manifested through the two parallel worlds of 1984 and 1Q84), the self-referential aspect and the author’s subtle involvement (channeled through the character of Tengo, who is a writer), and finally, intertextuality (demonstrated by allusions to George Orwell’s "1984").